A bad, bad day - Hall, Kirsten; Rader, Laura (New York, NY. : Scholastic, 1995)
A young boy's day starts badly, but his mood improves when his teacher gives him a good mark on his paper.
Cartwheel books
Preschool-grade 1
Ages 3-6
BR
Keywords: Schools -- Fiction; Stories in rhyme